EXPLORATIVE ANALYSIS AND STRUCTURED SPECULATION: RETHINKING COMPUTATIONAL DESIGN AS AN APPROACH FOR ARCHITECTURAL FORM EXPLORATION - Ferro Yudistira (Journal of Architecture & Environment, 2026)
This study examines the potential of computational thinking principles as an approach in architectural form explorations. This study proposes an alternative perspective in the computational design approach, which often emphasizes automation and optimization in problem-solving processes. Current research and discussion in computational design also tend to focus on algorithms as the main idea, overlooking other computational thinking principles. Using House IV—designed by Peter Eisenman—as a case, this study seeks to examine the possibilities of implementing computational thinking principles in a speculative form-making process. House IV was selected due to two main aspects related to its design process: 1) the involvement of rules and procedures, and; 2) the focus on architectural formal exploration instead of program. The processes consist of an analytical and a generative phase. Analytical phases employ three computational thinking principles—decomposition, pattern recognition, and generalization/abstraction—to deconstruct and identify the essential parts and underlying set of rules from House IV. The generative phase utilizes understanding from analysis – in the form of generalized rules – to build an algorithm to reconstruct variations of forms. This approach open possibilities for exploration/speculation of new or unique formal iterations while keeping the character and aesthetic quality of the House IV. Reflection on the processes highlights the importance of explorative analysis and structured speculation in architectural design methods. The findings show the importance of explorative aspect in the analytical phase, along with traceability and explicitness in generative phase of design process. This study proposes a more holistic implementation of computational thinking principles in speculative form-making exploration. This study solely focuses on architectural form exploration, without any consideration for other elements such as space, context and program/function.